Revolutionary War weapons [videorecording (DVD)] - Powell, Stuart (Filmmaker); Powell, Stuart (Filmmaker); Boffey, Mercer, 1982- (PBS, 2025)
In 1775, a ragtag army of farmers and tradesmen defeated the most powerful army in the world to win American independence. What military technology did the American colonies use in their fight for freedom, and how did it help propel them to one of history's most unlikely victories? Archaeologists and historians uncover the real stories of innovation, skill, and strategy that determined the outcome of important battles. From the Brown Bess musket to the world's first military submarine, get a close-up look at the powerful and sometimes ingenious weapons that helped win independence.